2008
DOI: 10.18388/abp.2008_3085
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of vitamin D receptor gene polymorphisms with bone mineral density in young women with Graves' disease.

Abstract: Graves' (GD) hyperthyroidism induces accelerated bone turnover that leads to decreased bone mineral density (BMD). The role of the VDR gene in predisposition to primary osteoporosis has been recognized. Recent studies show associations between the VDR gene polymorphisms and susceptibility to autoimmune diseases. Here we analyzed if VDR gene polymorphisms: BsmI, ApaI, TaqI, and FokI may predispose women with Graves' hyperthyroidism to BMD reduction or to disease development. The subjects were 75 premenopausal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…We hypothesized that this inconsistency might imply a role for vitamin D in light of evidence suggesting its potential link to both thyroid autoimmunity and glucose intolerance individually. In specific, it has been reported that allelic variations within the VDR gene may mediate susceptibility to thyroid autoimmunity [ 15 , 16 ]. Vitamin D insufficiency has been associated with thyroid autoimmunity [ 17 ], serum 25(OH)D levels were found to be significantly lower in patients with thyroid autoimmunity compared to controls [ 18 , 19 ], and the severity of 25(OH)D deficiency correlated with thyroid antibody levels in both adult [ 18 , 19 ] and children populations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that this inconsistency might imply a role for vitamin D in light of evidence suggesting its potential link to both thyroid autoimmunity and glucose intolerance individually. In specific, it has been reported that allelic variations within the VDR gene may mediate susceptibility to thyroid autoimmunity [ 15 , 16 ]. Vitamin D insufficiency has been associated with thyroid autoimmunity [ 17 ], serum 25(OH)D levels were found to be significantly lower in patients with thyroid autoimmunity compared to controls [ 18 , 19 ], and the severity of 25(OH)D deficiency correlated with thyroid antibody levels in both adult [ 18 , 19 ] and children populations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Na skutek nadczynności tarczycy w układzie kostnym można dostrzec przyspieszenie procesów anabolicznych, jak i katabolicznych [1]. W wyniku zmienionego metabolizmu tkanki kostnej dochodzi do wzrostu liczby osteoklastów i aktywności osteoblastów, jednakże procesy resorpcji kości przeważają nad tworzeniem tkanki kostnej [10,20]. Objawy osteoporozy widoczne są w kościach wyrostków zębodołowych [1,20].…”
Section: Wpływ Zaburzeń Funkcji Tarczycy Na Stan Uzębienia U Dzieci Ounclassified
“…W wyniku zmienionego metabolizmu tkanki kostnej dochodzi do wzrostu liczby osteoklastów i aktywności osteoblastów, jednakże procesy resorpcji kości przeważają nad tworzeniem tkanki kostnej [10,20]. Objawy osteoporozy widoczne są w kościach wyrostków zębodołowych [1,20]. W obrazie histopatologicznym można stwierdzić zwyrodnienie ozębnej oraz zaburzenie układu oraz degenerację włókien kolagenowych, co może prowadzić do utraty zębów.…”
Section: Wpływ Zaburzeń Funkcji Tarczycy Na Stan Uzębienia U Dzieci Ounclassified
“…Inadequate levels of vitamin D can lead to decreased calcium absorption and serum concentration. 12 The hormonal form of vitamin D is 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ], which bound to the vitamin D-binding protein (DBP), can be delivered to the various vitamin D target cells that use the VDR to retain the hormone. 13 The first gene identified to be associated with an osteoporosis-related phenotype was the VDR gene.…”
Section: Vitamin D Receptor Genementioning
confidence: 99%